A balanced perspective on the affordance of a gamified HRM system for employees' creative performance - Ikhide, Juliet Eyore; Timur, Ahmet Tarik; Ogunmokun, Oluwatobi A. (Emerald Group Publishing Ltd, 2023)
Purpose Rather than overstating the favorable effects of gamification on work outcomes, the purpose of this paper is to present a more balanced perspective into the effects a gamified human resource management (HRM) system may have on creativity at work. This conceptual paper explores and delineates how employees' interaction with gamification features within a gamified HRM system enables and particularly undermines employees' motivation for workplace creative performance. Design/methodology/approach The cross-disciplinary nature of this paper necessitates the reliance on theoretical principles, the explanatory and predictive capacities of theories central to human-computer interaction, employee motivation and creativity fields. Thus, the tenets of affordance, self-determination and dynamic componential theory were utilized to analyze the affordance of a gamified HRM system for employees' creative outcomes. Findings It is discovered that augmenting the HRM system with gamification affordance is crucial amid global market change and increasing digitization. However, incorporating game design elements into work systems does not necessarily guarantee an increase in creative outcomes. On the contrary, the system may equally undermine employees' motivation, which in turn hampers their creative outcomes. Originality/value Many gamification papers have more often than not touted the positive effects of such a system on the targeted outcome. Based on the affordance theory which shows that a user's interaction with gamification properties could produce different outcomes (not only favorable ones) and considering the intricacies of employees' motivation and behavioral outcomes at work, this paper takes a more balanced perspective to examine how gamification could generate intended as well as unintended consequences for employees' creativity, which is crucial to overall job performance.
Keywords: Gamification; Employee creativity; Motivation; Gamification affordance; Undermined motivation